2023
DOI: 10.3390/agronomy13082110
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Soil Nitrogen Retention Capacity by Biochar Incorporation in the Acidic Soil of Pomelo Orchards: The Crucial Role of pH

Abstract: Biochar is commonly used to improve acidic soil and reduce nitrogen loss. However, the impact of biochar on soil nitrogen retention, especially at varying pH levels, is not fully understood. Soil samples were obtained from an acidic red soil citrus orchard. The soil pH was adjusted using CaO, with five levels (4.0, 5.1, 5.8, 6.6, and 7.2), and two biochar doses (0% and 1%) were applied. The study used 15N-Tracer and Ntrace to investigate biochar’s influence on soil nitrogen retention at different pH levels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…In our study, both soil N mineralization and nitrification rates showed a significant positive correlation with DOC content (Figure S1). It is widely recognized that the process of soil nitrification leads to the production of NO 3 − , which reduces soil pH (Qian et al, 2023;Zhou et al, 2023). In our study, soil net nitrification rates were significantly decreased after the incorporation of biochar, especially those produced at low temperatures (Figure 3c).…”
Section: Effects Of Biochar Application On Soil N Contents and N Tran...supporting
confidence: 50%
“…In our study, both soil N mineralization and nitrification rates showed a significant positive correlation with DOC content (Figure S1). It is widely recognized that the process of soil nitrification leads to the production of NO 3 − , which reduces soil pH (Qian et al, 2023;Zhou et al, 2023). In our study, soil net nitrification rates were significantly decreased after the incorporation of biochar, especially those produced at low temperatures (Figure 3c).…”
Section: Effects Of Biochar Application On Soil N Contents and N Tran...supporting
confidence: 50%
“…When incorporated into the soil, biochar has the capacity to increase the overall pH of the soil [75]. Simultaneously, adding different concentrations of biochar to the soil induces changes in the pH value, with an increase corresponding to the applied level [76]. These findings are supported by the results of Hailegnaw et al [77], who noted that the highest biochar application rate (8%) was more effective in altering soil properties than lower biochar rates, significantly increasing pH in all incubated soils.…”
Section: Effects Of Biochar and Biochar With Amf On Soil Chemical Pro...mentioning
confidence: 99%
“…Nitrogen can be lost from the soil through processes such as leaching, denitrification, and volatilization, which lead to acidification in terrestrial systems, eutrophication of aquatic systems, and decline in biodiversity and contribute to climate change. The most commonly proposed solutions involve optimizing fertilizer doses, as well as considering the form of fertilizers used, such as slow-release fertilizers [6][7][8][9][10][11][12][13][14]. A very promising solution is the application of nitrification inhibitors [15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…Biochar is the most intensively investigated amendment and is widely described in the literature, including in the 'Soil and Plant Nutrition' section [6,[21][22][23][33][34][35][36][37][38][39]. Many review papers (1327 reviews indexed in the Web of Science Core Collection in categories related to agronomy) and meta-analyses have already been written on this subject [40][41][42][43][44][45][46][47][48].…”
mentioning
confidence: 99%